2009
DOI: 10.1021/la901072z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Oxygen Plasma Nanotexturing of Organic Polymer Surfaces: From Stable Super Hydrophilic to Super Hydrophobic Surfaces

Abstract: Plasma processing is used to fabricate super hydrophilic or super hydrophobic polymeric surfaces by means of O2 plasma etching of two organic polymers, namely, poly(methyl methacrylate) (PMMA) and poly(ether ether ketone) (PEEK); a C4F8 plasma deposition follows O2 plasma etching, if surface hydrophobization is desired. We demonstrate high aspect ratio pillars with height ranging from 16 nm to several micrometers depending on the processing time, and contact angle (CA) close to 0 degrees after O2-plasma treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
277
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(301 citation statements)
references
References 40 publications
14
277
0
10
Order By: Relevance
“…Some groups have also investigated the aging behaviour of oxygen plasma treated PMMA surfaces for different periods of times. Both Schmalenberg et al 8 and Tsougeni et al 9,23 reported that the hydrophobic recovery begun almost immediately after relatively short exposure (30 s-5 min). On the other hand, longer treatments (20 min-60 min) were reported to make the surface superhydrophilic for several days.…”
Section: B Pmmamentioning
confidence: 98%
See 2 more Smart Citations
“…Some groups have also investigated the aging behaviour of oxygen plasma treated PMMA surfaces for different periods of times. Both Schmalenberg et al 8 and Tsougeni et al 9,23 reported that the hydrophobic recovery begun almost immediately after relatively short exposure (30 s-5 min). On the other hand, longer treatments (20 min-60 min) were reported to make the surface superhydrophilic for several days.…”
Section: B Pmmamentioning
confidence: 98%
“…[6][7][8][9]21,23,36 Several studies 9,21,23 have demonstrated that longer treatment times induce more hydrophilic surfaces. Similar results have been observed for higher plasma powers as compared with lower ones, 6 implicating that the higher the plasma dose the lower the measured contact angle.…”
Section: B Pmmamentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from a flat surface, within minutes one can get a rough surface, and finally a porous rough layer. X ray photoelectron Spectroscopy (XPS) analysis shown in figure 2b, reveals relatively large surface concentration of Aluminum present in Oxide form (35) coming from sputtering of the Alumina dielectric dome, and the anodized Aluminum clamping ring of the etch tool. This "hard" etch inhibitor creates micromasking and leads to the development of nanotexture.…”
Section: Plasma Nanotexturing and The Role Of Reactor Wallsmentioning
confidence: 99%
“…Among the different methods, plasma treatment of a polymer surface is an effective technique because of its unique ability to form a thin hydrophobic film on surfaces [5]; this technique can be integrated into continuous production processes [6] also, which means a single-step method for surface modification. Plasma treatment of polymer surface is a well-established technique [7][8][9].…”
Section: Introductionmentioning
confidence: 99%